Outcomes of Conservative Management of Fingertip Injury in Paediatric Population - Majid Hussain, Asadullah Awan, Muhammad Ali Adnan, Masroor Ahmad, Farhan Zahid, Jameeat Mal (Pakistan Journal of Medical & Health Sciences, 2022)
In infants and children, the fingertip injuries occur frequently by accident which result causing infliction which ranges from a little cut to a fracture and also the finger amputation thus requires an immediate treatment intervention to avoid deformities. Different therapeutic approaches have been used involving surgical or conservative treatment. The conservative treatment is considered to be superior choice for management of these injuries so this research was designed to evaluate the functional and aesthetic outcomes of conservative approaches for treating fingertip injuries. Methods: This research consists of 30 children admitted to Ziaudin Hospital, Karachi with Allen’s type II and III of fingertip injuries divided into three groups based on the treatment approach including Platelet Gel treatment group (group I), Fucidic acid treatment group (group II), Hyaluronic acid treatment group (group III). Results: All the conservative treatment approaches showed promising improvement regarding the range of motion, healing time, aesthetic and sensory outcome, complications, and subjective satisfaction. However, the platelet gel group exhibits significantly short healing time (p=0.003) in comparison to Fucidic acid and Hyaluronic acid treatment group Conclusion: It was concluded that conservative treatment is one of the effective approach in management of fingertip injuries in paediatric population providing better functional, sensory and aesthetic outcomes. Keywords: Fingertip injuries, Conservative treatment, Outcomes